Analysis of Bone Healing in a Postoperative Patient: Skeletal Evidence of Medical Neglect and Human Rights Violations1. Issue 4 (28th March 2013) - Báez‐Molgado, Socorro; Peñaloza, Abigail Meza; Spradley, M. Katherine; Bartelink, Eric J.
Abstract This study highlights complexities associated with postsurgical trauma interpretation of a 76‐year‐old female patient from a psychiatric institution in Mexico. The skeletal analysis identified complications from an unsuccessful surgical operation for an intertrochanteric fracture of the femur. An improperly placed surgical plate resulted in nonunion due to limited contact between fracture margins. However, it is unclear whether this resulted from surgical complications, ineffective postoperative care, or from the decedent's limited ability to follow postoperative care instructions. Additionally, failure of the plate resulted in degenerative changes to the acetabulum. These complications, associated with degenerative changes to upper limb joints, suggest significant mobility issues. The pattern of antemortem trauma and contextual information support a conclusion of postoperative medical neglect, a documented problem in psychiatric institutions in Latin America. This study provides insight into the relevance of detailed trauma assessment of skeletal remains in cases where neglect and human rights violations are suspected.